Clinical impact of perioperative myocardial infarction after pancreatic surgery - Dovzhanskiy, Dmitriy I.; Hackert, Thilo; Krumm, Jens; Hinz, Ulf; Roggenbach, Jens; Hofer, Stefan; Büchler, Markus W.; Werner, Jens (Journal of gastrointestinal surgery, 2014)
The aim of this study was to evaluate the incidence, clinical impact and outcome of perioperative myocardial infarction (PMI) in patients undergoing pancreatic surgery.
Gesehen am 03.09.2020